2016
DOI: 10.1111/maec.12317
|View full text |Cite
|
Sign up to set email alerts
|

Combined stomach content and δ13C/δ15N analyses of oilfish, escolar, snake mackerel and lancetfish in the western North Atlantic

Abstract: Large, mesopelagic teleost fishes have a potentially keystone position in the ecology of the pelagic water column, yet remain relatively unstudied when compared with large, commercially important, epipelagic fishes. Here, the ecological roles of four, large, vertically migrating teleosts were examined. Stomach content analyses were performed on 48 oilfish (Ruvettus pretiosis), 35 escolar (Lepidocybium flavobrunneum), 32 snake mackerel (Gempylus serpens) and seven lancetfish (Alepisaurus spp.) collected from pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Our results therefore highlight how essential insights from stable isotope analysis had proven to complement stomach content data, in order to fully apprehend the variability in feeding habits of consumers. Similar conclusions have been presented by recent studies (Carassou et al, 2016 andKeller et al, 2016;Olson et al, 2016). Stomach contents indeed only provide very short-term information on consumer's diet, while isotopic ratios in the tissues reflect dietary habits over longer time scales (Cortés, 1997;Hobson, 1999;Post, 2002;Olson et al, 2016).…”
Section: Petimba) Greater Lizardfish (Saurida Tumbil) Long Raker Trsupporting
confidence: 86%
See 1 more Smart Citation
“…Our results therefore highlight how essential insights from stable isotope analysis had proven to complement stomach content data, in order to fully apprehend the variability in feeding habits of consumers. Similar conclusions have been presented by recent studies (Carassou et al, 2016 andKeller et al, 2016;Olson et al, 2016). Stomach contents indeed only provide very short-term information on consumer's diet, while isotopic ratios in the tissues reflect dietary habits over longer time scales (Cortés, 1997;Hobson, 1999;Post, 2002;Olson et al, 2016).…”
Section: Petimba) Greater Lizardfish (Saurida Tumbil) Long Raker Trsupporting
confidence: 86%
“…In this context, stable isotopes of carbon ( 13 C/ 12 C, or δ 13 C) and nitrogen ( 15 N/ 14 N, or δ 15 N) are the most often measured in food web studies (Hobson, 1999;Post, 2002). The combination of stomach content with δ 13 C and δ 15 N analyses is now recognized as a pertinent methodology in order to quantify fish diet and address its spatial and temporal variability in a given ecosystem (Hamidan et al, 2016;Keller et al, 2016;Malek et al, 2016;Olson et al, 2016;Weidner et al, 2017). In addition to carbon and nitrogen isotopic ratios, sulfur isotopes are also useful to trace the origin of the prey consumed by consumers in aquatic ecosystems (Peterson, 1999;Post, 2002;Fry and Chumchal, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The stable isotope values were then compared to literature values for potential prey; additional pelagic fish species’ δ 13 C and δ 15 N were used due to the logistical difficulties associated with physically collecting some specimens (e.g., small pelagic shrimp, squid species, isopods) while aboard the cooperating commercial pelagic longline fishing vessels. Several studies have already reported values for some prey items, such as Atlantic herring, pelagic squids, and Atlantic flying fishes (e.g., Estrada et al., ; Rau et al., ), or co‐occurring predators, such as mesopelagic fishes (Keller, Hirons, & Kerstetter, ).…”
Section: Methodsmentioning
confidence: 99%